Echocardiographic characteristics in Fontan patients before the onset of protein‐losing enteropathy or plastic bronchitis. Issue 1 (29th October 2017) - Du Bois, Florian; Stiller, Brigitte; Borth‐Bruhns, Thomas; Unseld, Bettina; Kubicki, Rouven; Hoehn, René; Reineker, Katja; Grohmann, Jochen; Fleck, Thilo
Abstract : Background: It was this study's objective to evaluate the echocardiographic characteristics and flow patterns in abdominal arteries of Fontan patients before the onset of protein‐losing enteropathy (PLE) or plastic bronchitis (PB). Design: In this retrospective cohort investigation, we examined 170 Fontan patients from 32 different centers who had undergone echocardiographic and Doppler ultrasound examinations between June 2006 and May 2013. Follow‐up questionnaires were completed by 105 patients a median of 5.3 (1.5–8.5) years later to evaluate whether one of the complications had occurred since the examinations. Results: A total of 91 patients never developed PLE or PB ("non‐PLE/PB"); they were compared to 14 affected patients. Eight of the 14 patients had already been diagnosed with "present PLE/PB" when examined. Six "future PLE/PB" patients developed those complications later on and were identified on follow‐up. The "future PLE/PB" patients presented significantly slower diastolic flow velocities in the celiac artery (0.1 (0.1–0.5) m/s vs 0.3 (0.1–1.0) m/s ( P  = .04) and in the superior mesenteric artery (0.0 (0.0–0.2) m/s vs 0.2 (0.0–0.6) m/s, P  = .02) than the "non‐PLE/PB" group. Median resistance indices in the celiac artery were significantly higher (0.9 (0.8–0.9) m/s vs 0.8 (0.6–0.9) m/s, ( P  = .01)) even before the onset of PLE or PB. Conclusion: An elevated flow resistance in the celiac artery may prevail in Fontan patients before the clinical manifestation of PLE or PB.